(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. This study aimed to determine diagnostic value of immunoperoxidase in comparison with immunofluorescence in the diagnostic assessment of kidney biopsy specimens. Materials and Methods. Forty-eight kidney biopsy specimens were used to compare a direct immunofluorescence technique with immunoperoxidase techniques on paraffin sections. The sensitivity and specificity were calculated. The kappa statistic for agreement between the two tests was categorized as poor (zero to 0.2), moderate (0.21 to 0.45), good (0.46 to 0.75), and almost perfect concordance (0.76 to 1.0). Results. Compared with immunofluorescence, the immunoperoxidase technique presented a sensitivity of 88.55% and a specificity of 69.22%. Its sensitivity in the staining for IgG, IgM, and IgA was 93.75%, 95.45%, and 76.47%, respectively. The specificity of this test in the staining for IgG, IgM, and IgA was 54.54%, 57.14%, and 96.00%, respectively. The overall kappa value was 0.60 and it was 0.60 for assessing staining intensity. There was a moderate agreement between immunoperoxidase and immunofluorescence in the positive or negative staining for IgG and IgM, as well as a good agreement in the positive or negative staining for IgA. For the staining intensity, the two tests had a good concordance for IgG and IgA and a moderate concordance for IgM. Conclusions. Although immunoperoxidase method has a lower overall diagnostic performance as compared to immunofluorescence, given the good concordance between the two techniques, it can be an alternative method for immunofluorescence study of kidney biopsy specimens, particularly where immunofluorescence fails or is not available.